Language Learners’ Motivation to Hungarian as a Foreign Language in Transcarpathia - Katalin Hnatyk; Гнатик Каталін; Hnatik Katalin (ДВНЗ «Переяслав-Хмельницький державний педагогічний університет імені Григорія Сковороди», 2018)
Резюме. Стаття зосереджується на ролі мотивація у вивченні іноземної мови і дає загальний концепт про терміни і види мотивації. Автор здійснював дослідження на тему мотивація учнів до угорської мови як іноземної. Результати дослідження показують, що учні мають інструментальні та інтегральні мотивації, у процесі вивчення даної іноземної мови.

Abstract. The article focuses on the role of motivation in foreign language learning. It gives a general concept about the terms and the types of motivation. The author carried out a mini-research on the Ukrainian language learners’ motivation to Hungarian as a foreign language.The results of the research show that they have both intrumental and integrative motivations to learn this foreign language.
Keywords: motivation; integrative motivation; instrumental motivation; attitude; foreign language; мотивація; інтегративна мотивація; інструментальна мотивація; аттитюд; іноземна мова